Infections of Two Isthmiophora Species (Digenea: Echinostomatidae) in Wild Mammals from Republic of Korea with Their Morphological Descriptions - Choe, Seongjun; Kim, Youngjun; Jeong, Dong-Hyuk; Yang, Jeong-Jin; Eom, Keeseon S. (Korean journal of parasitology, 2019)
Isthmiophora hortensis (Digenea: Echinostomatidae) is a dominant echinostome in animal reservoir hosts and humans in the Republic of Korea (Korea). We intended to investigate the infection status with this echinostome species in the several species of wild animals and describe the morphological characteristics in the faunistic view point. A total of 175 animal carcasses belonging to 3 families, i.e., Canidae, Felidae and Mustelidae, were collected from the southern regions of Korea from March 2010 to July 2017. Isthmiophora spp. worms were recovered from the small intestines of each animal under a stereomicroscope after washing of intestinal contents. Isthmiophora hortensis was recovered from 4 species of wild carnivores, i.e., Nyctereutes procyonoides (3/107: 2.8%), Mustela sibirica (11/31: 35.5%), Meles lucurus (2/3: 33.3%) and Martes flavigula (1/2: 50%). The other 3 carnivores comprising stray dogs, cat and leopard cat were negative for I. hortensis infection (0/2, 0/10 and 0/12, respectively). Specimens obtained from the Lutra lutra (6/8: 75%) were identified as a distinct species, I. inermis, by morphological comparison. Isthmiophora inermis has thinner body, elongate testes and different anterior limits of vitelline fields. Detailed morphological descriptions and comparisons with the morphological characteristics are provided. Conclusively, it was confirmed for the first time that 3 species of mustelid mammals, i.e., M. sibirica, M. lucurus, and M. flavigula, are to be the new definitive hosts of I. hortensis in Korea. Additionally, I. inermis is to be newly added in the Korean echinostome fauna.